2010
DOI: 10.1200/jco.2010.30.5334
|View full text |Cite
|
Sign up to set email alerts
|

Association of DNA Repair Gene Polymorphisms With Response to Platinum-Based Doublet Chemotherapy in Patients With Non–Small-Cell Lung Cancer

Abstract: Polymorphisms in the TP53 and PARP1 genes are involved in inter-individual differences in the response to platinum-based doublet chemotherapy in patients with NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 29 publications
0
50
0
Order By: Relevance
“…Nonetheless, the cytotoxic effects of platinum drugs may produce severe adverse effects, by damaging normal cells, which may hinder further treatment and impact outcomes. Differences in toxicities experienced and responses in patients who have received the same chemotherapy agent or regimen are commonly observed [10,11], and these are likely to be a result of polymorphic genetic variation in genes involved in drug metabolism and DNA repair and apoptosis [5,12]. Recently, numerous clinical studies have elucidated that genes involved in drug transportation, drug metabolism, DNA repair, and apoptosis may modulate platinum-based chemotherapeutic efficacy and drug-related toxicity outcomes [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the cytotoxic effects of platinum drugs may produce severe adverse effects, by damaging normal cells, which may hinder further treatment and impact outcomes. Differences in toxicities experienced and responses in patients who have received the same chemotherapy agent or regimen are commonly observed [10,11], and these are likely to be a result of polymorphic genetic variation in genes involved in drug metabolism and DNA repair and apoptosis [5,12]. Recently, numerous clinical studies have elucidated that genes involved in drug transportation, drug metabolism, DNA repair, and apoptosis may modulate platinum-based chemotherapeutic efficacy and drug-related toxicity outcomes [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Platinum (cisplatin or carboplatin) double-agent chemotherapy is the most common first-line treatment for patients with advanced NSCLC at present, and the efficacies of different combinations have been demonstrated to be similar in series of trials in unselected patients, with response rates of 30%-40% [5][6][7]. Standard treatment using platinum compounds induces both intrastrand and interstrand DNA adducts that result in bulky distortion of DNA and activates apoptosis signaling pathways, leading to cancer cell death [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The definite biological significance of this SNP is still unknown; but because of its location, it may affect the PARP-1 catalytic activity. Previous study suggested that Lys940Arg SNP may affect the response to chemotherapeutic agents in particular to DNA-damaging agents in patients with lung cancer (Shiraishi et al, 2010). However, this SNP was associated with increased risk of gastric cancer in Chinese population (He et al, 2012) and CRC in Singapore Chinese (Stern et al, 2007).…”
Section: Discussionmentioning
confidence: 88%
“…Further, the global expression pattern of the DNA repair proteins, such as PARP might have predictive implications in the adjuvant setting of NSCLC treatments. Interestingly, one study has linked a single nucleotide polymorphism (SNP) in the PARP1 gene with response of non-small cell lung cancers (NSCLC) to chemotherapy [24]. Our own recent studies have suggested that PARP1 tumor positivity might constitute a molecular context with theranostic interest when it is combined with ERCC1 and MSH2 status in NSCLC, with histological subtypes as possible subgroups that should be studied separately [3,25].…”
Section: Consequence Of Parp Inhibitionmentioning
confidence: 99%